Al-Kafāat At-Ta’līmiyyah wa Al-Mihniyyah li Mudarris Al-Lughat Al-‘Arabīyyah wa Ātsaruhā fī Natāij Ta’allum Al-Lughat Al-‘Arabīyyah lī Tullābi Al-Madrasah Ats-Tsānawiyyah Al-Islāmiyyah Al-Mutakāmilah Nūrul Ilmi - Daulay, Rafia Husna Zalzabila; Yufni Faisol; Hanomi (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research aims to discuss Pedagogic and Professional Competence of teacher and determine the extent and effects of the Pedagogic and Professional Competence of the Arabic language teacher from Nurul Ilmi Integrated High School on the Arabic language learning score for tenth grade students. the results are based on the questionnaire about pedagogic and professional competence’s score respondent. the Pedagogic and Professional Competence of the Arabic language teacher from Nurul Ilmi Integrated High School was very good, and the Arabic language learning score for tenth grade students are very good with total score 5963 and median students’ score 91,75 The Pedagogic competence (x1) and professional competence (x2) for the Arabic language learning score(y) of the students are 0.813, which indicates that there are strong effects, and the ratio of the variable (x1) and the variable (x2) = (0.813)2 x 100% = 67%. The researcher found that there are effects of the Pedagogic and Professional Competence of the Arabic language teacher from Nurul Ilmi Integrated High School on the Arabic language learning score for tenth grade students, with a percentage range of 67% or (Ha) acceptable.